Comparative Features of the Upper Alimentary Tract in the Domestic Fowl (Gallus gallus domesticus) and Kestrel (Falco tinnunculus): A Morphological, Histochemical, and Scanning Electron Microscopic Study. (February 2021) - Alsanosy, Abdallah A.; Noreldin, Ahmed E.; Elewa, Yaser H. A.; Mahmoud, Sahar F.; Elnasharty, Mohamed A.; Aboelnour, Asmaa
Abstract: The avian alimentary tract has evolved into different histologic structures to accommodate the physical and chemical features of several food types and flight requirements. We compared the esophagus, proventriculus, and gizzard of the domestic fowl, Gallus gallus domesticus (GGD) and kestrels, Falco tinnunculus (FT) using immunohistochemistry and scanning electron microscopy with various stains and lectins [ Dolichos biflorus agglutinin (DBA) and Ricinus communis agglutinin I (RCA120 )], and α -smooth muscle actin ( α -SMA). The esophagus of GGD demonstrated thickened epithelium, muscularis mucosae, and inner circular longitudinal tunica muscularis layers; moderate outer longitudinal tunica muscularis layers; and a true crop. In contrast, the esophagus of FT showed a thin epithelium, no muscularis mucosae, moderate inner longitudinal and thick outer circular tunica muscularis layers, and no true crop. In the proventriculus, the nature of the secretion in GGD was neutral, but that of FT was acidic and neutral. In the gizzard, the muscle coat of GGD by α -SMA had no muscularis mucosae, unlike FT, which had muscularis mucosae. In summary, there are many histologic differences between GGD and FT to meet their different physiologic needs, such as feeding.